Is the groundwater of Dhaka city, Bangladesh contaminated with naturally occurring potential toxic elements? - Mahir Tajwar; Mahfuzur Rahman; Mahfuzur Rahman; Shamiha Shafinaz Shreya; Nazmus Sakib; Md. Yousuf Gazi; Md. Yousuf Gazi; Mahmudul Hasan; Anika Samm-A; Anwar Zahid (Frontiers in Environmental Science)
This study investigates the contamination of groundwater in Dhaka City, Bangladesh, focusing on six potentially toxic elements, including As, Cu, Mn, Cr, Al, and B, due to their implications for public health as groundwater serves as the primary source of drinking water in the region. 15 samples were taken into consideration and was analyzed for six elements (As, Cu, Mn, Cr, Al, and B) using an Atomic Absorption Spectrophotometer (AAS). Arsenic (As) and chromium (Cr) were undetectable in all samples. The average concentrations of Copper (Cu), Aluminum (Al), Boron (B), and Manganese (Mn) were measured at 0.075 mg/L, 0.087 mg/L, 1.14 mg/L, and 0.48 mg/L, respectively. Among these, only one sample (S-05) exceeded the WHO (2022) drinking water limits for Boron, and 10 samples surpassed the limits for Manganese. Pollution indices like MEI, NI, and Cd were used to evaluate contamination levels, revealing significant pollution in multiple samples. Metal evaluation index (MEI) values were found between 0.39 and 17.97 with the average of 6.71. The average values of the Nemerow pollution index (NI) and degree of contamination (Cd) were found sequentially to be 4.35 and 5.71. In both cases, eight samples were found to be highly contaminated. The observed hazard index (HI) values for adults varied from 0.20 to 2.47, whereas for children it ranged from 0.32 to 3.93. All samples indicate values of children exceed the HI values of adults which indicates that children are more susceptible than adults through oral exposure to drinking water. The elevated concentrations of manganese were the primary cause of the higher NI, Cd, and HI values in eight samples. This study highlights groundwater contamination as a critical public health concern and advocates the need for mitigation efforts to ensure safe drinking water access. The study underscores the urgent need for implementing stricter groundwater management policies and public health interventions to mitigate contamination risks.